Alienação eleitoral no Brasil: votos brancos, nulos e abstenções nas eleições presidenciais (1989-2002) - Costa, Homero de Oliveira (2006)
This Study aims at analyzing electoral alienation, this is, white and null voting as well as voting abstention at Brazilian presidential elections from 1989 to 2002. The used methodology was data collecting in each state and region. Firstly, a review on international electoral bahavior studies, mainly from Europe, the United States and Latin America, was carried out showing that there is a growth one of the electoral alienation items, voting abstention. Is this chapter it will be shown some models and/or theories along with their respective explanations (Columbia and Michigan, theories on rational choice, social integration, etc.). It is observed that although the growth on voting abstention is a constitutive part of electoral behavior in most of those estudied countries there is no model and/or theory which would isolated explain this. Its should be taken into account in the analysis several factors as well as to establish differences not only among continentes as in Europe and Latin America. But no matter the differences among the countries what seems to go on worldwide is a political party crisis as well a political representation crisis which without this the electoral alienation can not be understood. In other words, this political representation has to be more widely considered within this crisis. Data on electoral alienation considering abstention as well as null and white voting also showed a disbelieving and a non-legitimacy of political parties. For the Brazilian context, the electoral behavior and the political party crisis as well as their political representation were analyzed by a pertinent literature review specifically the one postl964. Finally, at the results of each analyzed electoral year there is an introdution on the political-electoral context. Afterwards, data are shown using for each defined variable linear regression model by minimum square method. Conclusion shows that each HDI (Human Developing Index) and SEI (Social Exclusion Index) variables montly explain the null and white voting while territorial extension also mostly explains electoral abstention. However it was shown that isolated factors do not explain electoral alienation rating thus it is also needed to consider other factors such as the political context organization (more competing election consequentely lower electoral alienation rate) and the role od media within the respective electoral processes (wider broadcasting thus more participation and lower alienation rate) which are inserted in a more general view of the party crisis as well as the political representation